Vex, hex, smash, smooch : let verbs power your writing - Hale, Constance (W.W. Norton & Co., 2012)
Helps aspiring writers understand the importance of using powerful verbs in their work through examples of brilliant writing and presents a linguistic history to demonstrate how language and writing has evolved over time.